The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physrevb.83.174433
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of the giant ferroelectric distortion and pressure-induced spin-state transition in BiCoO3

Abstract: Using configuration-state-constrained electronic structure calculations based on the generalized gradient approximation plus Hubbard U method, we sought the origin of the giant tetragonal ferroelectric distortion in the ambient phase of the potentially multiferroic material BiCoO3 and identified the nature of the pressure induced spin-state transition. Our results show that a strong Bi-O covalency drives the giant ferroelectric distortion, which is further stabilized by an xy-type orbital ordering of the high-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Taking into account the strong Coulomb repulsion ( U ) between the localized d states of Fe, we choose the GGA+ U approach to describe the correlation effects in transition metal oxides. In the present work, the GGA+ U approach described by Dudarev et al was applied , where an effective Hubbard parameter U eff = U – J is 4 eV for Fe atom .…”
Section: Methodssupporting
confidence: 94%
“…Taking into account the strong Coulomb repulsion ( U ) between the localized d states of Fe, we choose the GGA+ U approach to describe the correlation effects in transition metal oxides. In the present work, the GGA+ U approach described by Dudarev et al was applied , where an effective Hubbard parameter U eff = U – J is 4 eV for Fe atom .…”
Section: Methodssupporting
confidence: 94%
“…The XAS study by Sudayama et al . revealed that the strong Bi–O covalency results in smaller crystal field splitting than that in Sr 2 CoO 3 Cl isostructural with Sr 2 CoO 3 F404142, which could be expected from the larger distance between the Co cation and the CoO 4 basal plane for BiCoO 3 ( D  = 0.74 Å) than those for Sr 2 CoO 3 Cl ( D  = 0.33 Å) and Sr 2 CoO 3 F ( D  = 0.25 Å). In Sr 2 CoO 3 F, it is likely that the primarily weak interaction between the Co and F ions and the relatively small distortion of CoO 5 pyramid facilitate the gradual and complete spin state change from the HS state to the LS state.…”
Section: Resultsmentioning
confidence: 90%
“…However, in comparison with coordination complexes adopting rich variety of ligands, the selectivity of ligands is highly restricted in metal oxides. In fact, the approach frequently employed is cation substitution that indirectly distorts octahedral symmetry, as in 6-coordinated Pr 0.5 Ca 0.5 CoO 3 1516 and 5-coordinated BiCoO 3 1718. In this context, the study on the effect of anion substitution on spin state changes is of value for further understanding the chemistry of Co(III) cation.…”
mentioning
confidence: 99%
“…For example, the moment of the case with 4% in-plane strain is about 4.8 μB, which is almost twice larger than the case with 4% out-of-plane strain. The change in magnetic moment is usually related to the different d electrons occupation, which have been found that strains can change the d electrons occupation31. To show this is indeed the case.…”
Section: Resultsmentioning
confidence: 91%